Factors Affecting Maternal Birth Preparedness: Evidence from Salatiga, Cental Java - Yuliana, Ana; Murti, Bhisma; Prasetya, Hanung (Journal of Maternal and Child Health, 2019)
Background: Maternal unpreparedness in facing childbirth is one of the factors causing the high maternal mortality rate (AKI). To support efforts to accelerate the reduction of MMR, preparation of childbirth is an important matter that must be improved. Pregnant women class is an activity to prepare the mother physically and psychologically in facing the delivery. The purpose of this study was to determine the factors that influence preparation for childbirth in pregnant women, including: the role of midwives, motivation of pregnant women and utilization of pregnant classes.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted in 6 community health centers in Salatiga, from June to July 2018. A sample of 120 mothers was selected by total sampling. The dependent variable was birth preparation. The independent variables were motivation, midwife role, and utilization of pregnant class. The data were collected by questionnaire and analyzed by a multiple linear regression.Results: Birth preparedness was increased with strong midwife role (b= 2.82; 95% CI= -0.45 to 5.68; p= o.054), strong motivation (b= 4.12; 95% CI= 0.97 to 7.27; p= 0.011), and utilization of pregnant class (b= 3.90; 95% CI= 0.66 to 7.13; p= 0.019).Conclusions: Birth preparedness is increased with strong midwife role, strong motivation, and utilization of pregnant class.Keywords: birth preparedness, motivation, midwife role, pregnancy class, pregnant womenCorrespondence:Ana Yuliana. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: aishabilqisnugroho@gmail.com. Mobile: +62139321543.Journal of Maternal and Child Health (2019), 4(1): 55-61https://doi.org/10.26911/thejmch.2019.04.01.08